2008
DOI: 10.1677/joe-08-0127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with 8-prenylnaringenin and oral estradiol on the GH–IGF-1 axis and lipid metabolism in rats

Abstract: After the heart and estrogen/progestin replacement study and the women's health initiative study, the prospect of hormone replacement therapy (HRT) on cardiovascular diseases (CVD) has changed dramatically. These findings led to various attempts to search for alternatives for classical HRT, e.g. phytoestrogens.The flavanone 8-prenylnaringenin (8-PN) was identified as a phytoestrogen with strong estrogen receptor-a activity. As the pituitary and the liver are targets for estrogen action, we assessed the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…With our experimental protocol, estrogen treatment led to increased levels not only of triglycerides and HDL, but also of LDL and total cholesterol concentrations, whereas Böttner et al reported that oral administration of estrogen decreased total cholesterol, LDL and HDL, and increased triglyceride levels in OVX rats [28]. These discrepancies may be related to the different experimental designs, in particular the different modes of estrogen administration.…”
Section: Discussionmentioning
confidence: 71%
“…With our experimental protocol, estrogen treatment led to increased levels not only of triglycerides and HDL, but also of LDL and total cholesterol concentrations, whereas Böttner et al reported that oral administration of estrogen decreased total cholesterol, LDL and HDL, and increased triglyceride levels in OVX rats [28]. These discrepancies may be related to the different experimental designs, in particular the different modes of estrogen administration.…”
Section: Discussionmentioning
confidence: 71%
“…Despite low sensitivity and poor selectivity, there have been a surprisingly large number of publications describing applications of HPLC-UV methods to the quantitation of prenylflavonoids in biological samples [21,23,64,67,69]. Except for the report by Avula et al [48] most of these studies did not show sample chromatograms, so it was not possible to determine the reliability of such data.…”
Section: Other Separation Methodsmentioning
confidence: 99%
“…Except for the report by Avula et al [48] most of these studies did not show sample chromatograms, so it was not possible to determine the reliability of such data. We also note that only a few of these methods used an internal standard, despite dealing with a complex matrix and extensive sample preparation [69]. Overall, it is likely that in near future more sensitive and selective LC-MS-MS methods will replace HPLC-UV-based methods measurement of prenylflavonoids in biological samples.…”
Section: Other Separation Methodsmentioning
confidence: 99%
“…107 In in vivo studies, 8PN has an anti-atherosclerotic profile which may demonstrate its potential for the prevention of estrogen deficiency associated cardiovascular diseases. 108 After long-term treatment of three months with 8PN, decreased bw and an increased uterus weight were observed, as well as with estradiol benzoate. 108 In another three month experiment, OVX rats treated with 8PN share many effects in the uterus, vagina, and mammary gland with estradiol; at the same time, differences in the mechanism of action seem to exist.…”
Section: Estrogenic Effects Of Prenylflavonoids In Vivomentioning
confidence: 95%
“…108 After long-term treatment of three months with 8PN, decreased bw and an increased uterus weight were observed, as well as with estradiol benzoate. 108 In another three month experiment, OVX rats treated with 8PN share many effects in the uterus, vagina, and mammary gland with estradiol; at the same time, differences in the mechanism of action seem to exist. 109 Other experiments in OVX rats, as a model for hormone-dependent osteoporosis, demonstrated that 8PN can completely protect from ovariectomy-induced bone loss.…”
Section: Estrogenic Effects Of Prenylflavonoids In Vivomentioning
confidence: 95%